A probabilistic explanation of Pearson's correlation. (25th July 2019) - Liu, Xiaofeng Steven
Abstract: Pearson's product‐moment correlation can be explained by means of the probability of concordant pairs of observations on two continuous variables (ie, the order of the observations from two randomly selected individuals is the same between the two variables). The probability of concordant pairs features relatively easy computation and offers an alternative perspective on Pearson's correlations.